Erratum to “Influence of platelet content on the fabrication of colloidal gels for robocasting: Experimental analysis and numerical simulation” [J. Eur. Ceramic Soc. 40 March (3) (2020) 811–825](S0955221919307150)(10.1016/j.jeurceramsoc.2019.10.044) - Lorenz, Mylena Mayara; Dietemann, Bastien; Wahl, Larissa; Bierwisch, Claas; Kraft, Torsten; Kruggel-Emden, Harald; Travitzky, Nahum (Journal of the European Ceramic Society, 2020)
The publisher regrets that the location Wöhlerstraße in Bastien Dietemann's affiliation was incorrectly typeset in the above paper as Wöhlerstrabe and it should have been Wöhlerstraße. The publisher would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2020-02-21